2018
DOI: 10.1371/journal.pone.0199117
|View full text |Cite|
|
Sign up to set email alerts
|

Low-dose ionizing radiation exposure represses the cell cycle and protein synthesis pathways in in vitro human primary keratinocytes and U937 cell lines

Abstract: The effects of the high-dose ionizing radiation used in radiotherapy have been thoroughly demonstrated in vitro and in vivo. However, the effects of low-dose ionizing radiation (LDIR) such as computed tomography-guided biopsies and X-ray fluoroscopy on skin cells remain controversial. This study investigated the molecular effects of LDIR on the human primary keratinocytes (HPKs) and U937 cells, monocytes-like cell lines. These cells were exposed to 0.1 Gray (Gy) X-ray as LDIR. The modulation of transcription w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Ribosomal proteins can respond in different ways to IR exposure. Changes in the expression levels of proteins from this family as a result to exposure to IR have been reported [40,41], sometimes resulting in IR-sensitivity [42]. In addition, we detected proteins belonging to families that participate in dehydrogenase activity, such as Ldh, Aldedh, and ADH families.…”
Section: Resultsmentioning
confidence: 91%
“…Ribosomal proteins can respond in different ways to IR exposure. Changes in the expression levels of proteins from this family as a result to exposure to IR have been reported [40,41], sometimes resulting in IR-sensitivity [42]. In addition, we detected proteins belonging to families that participate in dehydrogenase activity, such as Ldh, Aldedh, and ADH families.…”
Section: Resultsmentioning
confidence: 91%
“…A recent in vitro study indicates that LDIR exposure of 100 mGy to primary keratinocytes and U937 (lymphoma) cell lines causes cell cycle arrest and impairs protein synthesis; however, the phase of the cell cycle in which the arrest occurs is not discussed [29].…”
Section: Normal Cellsmentioning
confidence: 99%
“…This would be a promising innovative solution for eliminating precancerous cells from the population through the LDIR-stimulated bystander effects. A recent study demonstrated that LDIR exposure on HPKs propagates effects that induce cell cycle arrest and protein synthesis repression in U937 cells; this bystander effect induced by LDIR in U937 cells is associated with increased expression of p21 Waf1 via TGFβ signaling and activation of p38 MAPK activation [29]. It is interesting to note that p53 plays an important role in communicating a stress response to neighboring cells, in addition to coordinating intrinsic and extrinsic cell signals [109].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in anti-inflammatory cytokines such as IL-4, IL-10, and reductions in inflammatory cy-tokines such as TFN-α have been observed at 50 mGy [158]; however, this effect has also been observed at higher doses of up to 1 Gy [25,159,160]. Of note, one study found that 100 mGy actually increased inflammatory cytokines [161], and another found that 100 mGy may have a negative effect on cognition, although noted further investigation is required [108]. Notably, 100 mGy appears to disrupt the BBB, which is a key aspect of neuroinflammation [74,162].…”
Section: Figurementioning
confidence: 99%